StatsCasts: screencasts for complementing lectures in statistics classes - Dunn, Peter K.; McDonald, Christine; Loch, Birgit (International journal of mathematical education in science and technology, 2015)
Students who are studying introductory statistics units but are enrolled in non-statistics majors often struggle with the content, and do not stay engaged. Support structures are in place at many Australian universities to help these students. Most of these are face-to-face support centres that the students can visit during opening hours. To provide additional assistance to these students any time, and from anywhere, online media are increasingly used by students - either provided by support centres, or sought independently by students. Little research has been undertaken on the effectiveness of such resources to support student learning. This paper investigates whether students will embrace StatsCasts - short screen-capture videos on key statistical topics that students have struggled with in the past, with narrator explanation provided by the lecturer - as part of their learning strategy and if they will actively engage with the videos. Students enrolled in a large first-year statistics class at an Australian university who had been provided with StatsCasts responded to a survey at the end of the semester. Volunteering students also participated in a focus group to probe deeper into students' perceptions of and motivations for watching the videos. Analysis of the data shows that students do actively engage with the StatsCasts and they appear to become an important component of their study and revision strategy.